Usos de la literatura en la publicidad - ESCRIBANO HERNÁNDEZ, Asunción (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2011)
Literature has always served to advertising as source of inspiration. Since the principal purpose of advertising is to obtain sales, it is not surprising that the creative ones are based on techniques that from the beginning had given samples of being the most aesthetic channel of transmission of ideas. To investigate the affirmed previously, we have analyzed a series of advertisements that in the last five years have used different literary elements. This has allowed us to conclude a series of functions played by literature that explain why is it for advertising a common resource and economically efficient.